Avaliação das características do esterco bovino reciclado usado como cama e seu efeito sobre a qualidade do leite de vacas em confinamento - Loman, Renata Thais (Universidade Estadual de Ponta Grossa, 2025)
Production cost in confinement systems in Brazil is one of the main challenges for dairy farming. Sawdust is the most common bedding material, but its cost and availability may vary. As an alternative, recycled manure (RM) has been used in free stall systems, although its risks and benefits remain unclear in Brazil, especially in the Center-Eastern region of Paraná. This study evaluated the use of RM in two experiments. In the first, five treatments were compared: sawdust without calcium oxide (CaO), sawdust + RM without CaO, sawdust + RM with CaO, RM without CaO, and RM with CaO. Materials were placed in mini-beds with six replications and evaluated over 30 days for dry matter (DM), pH, nitrogen (N), carbon (C), standard plate count (SPC), and microbiology. Significant interactions between treatment and time were observed for DM, N, C, pH, and SPC. Sawdust showed higher DM (55%) than RM (32%). Beds with RM had higher initial SPC (290,000 CFU/g) compared to sawdust (576 CFU/g), but values decreased with composting time. Temperature remained low in all treatments (24–20 oC). The second experiment, conducted on a dairy farm for 63 days, compared two bedding materials: RM and a 50% RM + sawdust mixture, both treated with Ca (OH)2 and CaO. Weekly analyses included DM, N, C, pH, SPC, microbiology, and milk yield/composition. There was an interaction between bedding type and sampling days. RM beds had lower DM (78%) than RM + sawdust beds (86%). By day 63, the RM + sawdust treatment showed higher SPC (334,000,800 CFU/g) compared to RM (334,000 CFU/g), suggesting greater contamination. The RM + sawdust treatment also showed a higher C:N ratio. Milk yield, composition, and gene expression related to mammary health did not differ between treatments. The addition of CaO and Ca(OH)2 and composting time improved RM quality. Under these conditions, RM bedding did not compromise mammary gland health, with an average somatic cell count of 61,000 cells/mL.
Keywords: Contagem padrão em placas; Contagem de células somáticas; Compostagem; Free stall; Microrganismos; Serragem